Wild Species from the Asteraceae Family, Traditionally Consumed in Some Mediterranean Countries - Ekaterina Kozuharova; Giuseppe Antonio Malfa; Rosaria Acquaviva; Benito Valdés; Daniela Batovska; Christina Stoycheva; Moh Rejdali; Pasquale Marino; Vivienne Spadaro (Plants)
Mediterranean countries represent a dynamic hub of cultural exchange, where wild plants play a significant role in culinary traditions. A substantial number of these plants belong to the Asteraceae family. The climate similarities across the region contribute to the common distribution ranges of the plants. While many species are widely distributed, others are confined to specific subregions, such as the western Mediterranean, eastern Mediterranean, or North Africa. Only six taxa of the traditionally consumed wild Asteraceae plants are endemic to just one country. This review focuses on wild plants from the Asteraceae family traditionally used as food across 13 study sites, comprising 11 countries in the Mediterranean and adjacent territories, including both mainland areas and three islands. The objective is to identify and analyze patterns of native distribution in relation to actual consumption. As a result, 167 edible wild plants from the Asteraceae family were identified. Their patterns of distribution and consumption are described and analyzed. The highest number of these edible wild plants from the Asteraceae family is consumed in Spain (n = 65), followed by southern Italy (n = 44) and Morocco (n = 32). A similar pattern of consumption is seen in Turkey (n = 24), Sicily (n = 23), Jordan and Palestine (n = 21), and Bulgaria (n = 21). It is notable that 106 plants are used as food in one particular country only, although most of them are distributed in several other countries. Many of the species consumed in certain countries are not used by neighboring populations, highlighting a limited cross-border transmission of ethnobotanical knowledge. The findings from a Jaccard index statistical analysis are discussed.